Peran Yayasan Lembaga Perlindungan Konsumen (Ylpk) Jatim Di Surabaya Dalam Mendampingi Konsumen Pada Sengketa Travel Haji Dan Umrah Prespektif Fiqih Muamalah - Danang Edi Susanto; Saiful Ibnu Hamzah (MAQASID, 2018)
ABSTRACKEvery year the problem of consumer protection is always occurred. Hajj and Umrah travel is the most problematic issue reported to the Consumer Protection Foundation (YLPK) of East Java in Surabaya. This study intends to find out how is the role of the Consumer Protection Foundation (YLPK) in assisting disputes between Hajj and Umrah travels, and how is the perspective of muamalah fiqh on the role of YLPK of East Java in assisting consumer protection in the dispute over Hajj and Umrah travel. This is a qualitative research with Normative and Doctrinal types. Data are collected by interviews, and documentation. Data verification is done through data validation at the East Java Consumer Protection Foundation (YLPK) in Surabaya.The results of this study are intended to determine the extent of the role of the Consumer Protection Foundation (YLPK) of East Java in Surabaya in assisting consumer protection in the dispute over Hajj and Umrah travel. The act in protecting consumer is given in order to get the rights of the consumer in mediation to the litigation process if needed. Keywords: Consumer protection, YLPK of East Java, Muamalah Fiqh.